Visible light triggered regioselective ring expansion of N-tosylaziridines: An efficient approach to 2-nitroazetidines. Issue 40 (4th October 2017) - Kapoor, Ritu; Tripathi, Shubhangi; Singh, Sachchida N.; Keshari, Twinkle; Yadav, Lal Dhar S.
Graphical abstract: Highlights: Highly regio- and diastereoselective ring expansion of N -tosylaziridines to 2-nitroazetidines. 1-Bromo-1-nitroalkanes as the ring opening and closing agent. The first synthesis of 2-nitroazetidines. Utilization of sustainable natural resources like visible light and air. Abstract: Visible light induced ring expansion of N -tosylaziridines with 1-bromo-1-nitroalkanes to afford 2-nitroazetdines in moderate to excellent yields with high regio- and diastereoselectivity is reported. The salient features of the protocol include the first synthesis of 2-nitroazetidines, operational simplicity, utilization of clean, inexpensive and sustainable resources like visible light and atmospheric oxygen under photoredox catalysis at room temperature in one-pot procedure.